In Silico Analysis of Sox2 Gene for Pluripotency Detection at Mouse Embryonic Fibroblast and induced Pluripotent Stem Cell (iPSC) - Aroem Naroeni; Seprianto; Kevin Febrianus Moda (Future Science)
Stem cells are cells that have not been specialized and have a specific characteristic compared to other cells. There are several transcription factors like Sox2, Oct4, c-Myc, and Nanog to maintain embryonic stem cells. In pluripotent stem cells, sex-determining region Y-box 2 (Sox2) is a critical transcriptional regulator, and for somatic cell reprogramming, which involves returning differentiated cells to a pluripotent embryonic state by reversing their epigenetic arrangement. This study aimed to design primers for detecting the Sox2 gene expressed in Mouse Embryonic Fibroblasts and induced Pluripotency Stem Cell as pluripotency detection in stem cell research. In silico analysis was carried out to detect ofx2gene by using several software such as BLAST to search sequence Sox2 gene from Homo sapiens and Mus musculus, Bioedit for sequence alignment, SnapGene for PCR in silico, and PrimerBlast for online primer design. Primer candidates successfully designed were then analyzed for their secondary structure using NetPrimer. The results showed that forward primer (5'- CTACAGCATGTCCTACTCGCA -3') and reverse primer (5'- ACTTGACCACAGAGCCCA -3') were selected primers for M. musculus. Also, forward primer (5’-CTACAGCATGTCCTACTCGCA-3') and reverse primer (5'- ACTT-GACCACCGAACCCA-3') for Homo sapiens. Detection by PCR in silico using templates from H. sapiens and M. musculus sequences showed that the primers could specifically amplify the Sox2 gene in each species. Nevertheless, laboratory experiments need to be carried out for preliminary validation that has been designed. These primers will be used to measure the gene expression of Sox2 in qRT-PCR to detect the stemness characteristic of stem cells.